Exploring gendered patterns and students’ needs at Morocco’s oldest college counseling center: implications for inclusive support services - Es-Sahib, Nabil; Takhdat, Kamal; Rafouk, Leila; Okhaya, Latifa (Frontiers in Education, 2025)
College counseling plays a vital role in supporting students’ academic success, mental health, and overall well-being. To date, no research has examined this topic among Moroccan students. This study investigates gendered patterns and needs among 401 Moroccan students accessing the country’s oldest college counseling center, located at the Semlalia Faculty of Sciences. This is a retrospective, quantitative study based on case file data collected from counseling records spanning 2015–2018. Descriptive and comparative analyses were conducted to explore visit patterns among the study participants. Men tend to seek counseling at a later age, primarily for academic-related concerns, whereas women are more likely to pursue non-pedagogical support and to participate in multiple counseling sessions. Furthermore, students’ origin, housing situation, and year of study are associated with differences in their counseling needs. Local students, those residing with family, and first-year students predominantly seek academic support, while non-local students, those living in shared housing, and students in advanced years are more inclined to request non-pedagogical assistance. These findings offer insights into gender disparities in student counseling, enhance the understanding of student support needs, and highlight the role of Morocco’s pioneering college counseling center in promoting students’ well-being. This study also lays the groundwork for future research on broader student populations and evolving counseling approaches.